Sinfully sexy a novel - Lee, Linda Francis (Random House Publication, 2004)
"Plain-Jane Chloe Sinclair has never been bad... until she stumbles- literally- into the arms of a gorgeous stranger. To make matters worse, her world is rocked completely off its axis the morning after when the sensual dreamboat turns out to be the man brought in to save the TV station where she works."--Back Cover.